2021
DOI: 10.1093/cid/ciab1033
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplementation Would Be Cost-Effective for Reducing Tuberculosis Incidence and Mortality in India: The Ration Optimization to Impede Tuberculosis (ROTI-TB) Model

Abstract: Background Undernutrition is the leading cause of tuberculosis (TB) in India and is associated with increased TB mortality. Undernutrition also decreases quality of life and economic productivity. Material and Methods We assessed the cost-effectiveness of providing augmented rations to undernourished Indians through the government’s Targeted Public Distribution System (TPDS). We used Markov state transition models to simulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…(13) Forth, the model did not capture the positive externalities of nutritional support, including improvements in nutritional status and functional recovery and improved economic productivity among TB survivors, which have been explored in a previous analysis. (26) Taken together, these limitations suggest that our ICER estimates will be conservative, and that nutritional support could be even more cost-effective than we project.…”
Section: Discussionmentioning
confidence: 86%
“…(13) Forth, the model did not capture the positive externalities of nutritional support, including improvements in nutritional status and functional recovery and improved economic productivity among TB survivors, which have been explored in a previous analysis. (26) Taken together, these limitations suggest that our ICER estimates will be conservative, and that nutritional support could be even more cost-effective than we project.…”
Section: Discussionmentioning
confidence: 86%
“…A survival analysis of TB deaths from the Tuberculosis Disease and Mortality Surveillance Information System in Zhejiang province, China, concluded that 71.1% of 283 deaths caused by TB occurred within three years of diagnosis and treatment (33). The main reason for this difference is that TB is closely related to body nutrition as a type of immune disease, and individual nutritional status is closely related to individual economic and socioeconomic status (34)(35)(36). Therefore, we discovered that the results of a prognostic model are different for TB patients in different regions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians have observed that many patients had malnutrition which might impact the treatment outcome. Nutritional supplementation can contribute to controlling TB and reducing mortality, as reported in India ( 8 ). Study has indicated that interventions with high-energy supplements such as a high-cholesterol diet, vitamins A and D, and multiple micronutrient supplements can help patients with active TB gain weight ( 9 ).…”
Section: Introductionmentioning
confidence: 94%
“…To our knowledge, few studies have evaluated and compared the utility of the NRS 2002 and GLIM for nutritional diagnosis of active PTB. Therefore, the present study aimed to provide the first evidence for malnutrition and further help to improve the outcome of patients with active PTB ( 8 ), especially for multidrug-resistant TB, which has represented the main challenge for TB control. We present this article in accordance with the TRIPOD reporting checklist (available at https://jtd.amegroups.com/article/view/10.21037/jtd-23-623/rc ).…”
Section: Introductionmentioning
confidence: 99%